Feel good, look good, Web good - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A CTA workshop in Guyana in December 2001 rounded a series of three training courses for the knowledge co-workers of agricultural information agencies on designing and maintaining their Websites. The two-week workshops on Web publishing were...